Catch your death - Child, Lauren (Child, Lauren. Ruby Redfort (Series), 2018)
Ruby Redfort knows how to survive--she can start fires, find water, and knows what kind of fungi will kill her if ingested--but all her survival training is worthless when nature has plans of its own.